PEDAGOGICAL CONDITIONS FOR DEVELOPING CREATIVE QUALITIES IN STUDENTS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
In modern education, the process of nurturing an independent, critical-thinking, and creative individual is being improved by incorporating new socio-pedagogical demands and principles. The ideas of independent thinking, creativity, and personality development have been at the core of pedagogical theories and the early stages of school development, aiming to shape socially significant subjects with aesthetic sensibilities. In later stages of human history, personal activity has been described as becoming more original and enriched with unique ideas. In this context, we will focus on the issues related to developing students' creative abilities.